Whole-rock chemical analyses from the Heldburg dyke swarm - Höhn, Stefan; Geyer, Gerd; Frimmel, Hartwig E; Millonig, Leo J.; Gerdes, Axel; v. Seckendorff, Volker (PANGAEA, 2025)
In the project "Geochemistry and geochronology of the Heldburg dyke swarm, Central European Volcanic Province" we conducted geochemical and geochronological investigations on mafic dykes and former magma chambers of the Heldburg dyke swarm. The latter is part of the Central European Volcanic Province and positioned in the South of Thuringia and the North of Bavaria (Germany). It consists of several hundred mafic NNE-SSW striking dykes with an usual thickness of < 1m and few former magma chambers. All of these have an atypical position within the Central European Volcanic Province located away from Hercynian massifs and major rift axes and were hitherto poorly investigated. In general, 10 different locations of the Heldburg dyke swarm were sampled for whole-rock analyses and 4 different locations were chosen for determining their apatite and zircon ages. The fieldwork was conducted between March 2022 and December 2023. The analytical work was done between June 2022 and April 2024 at the Department of Geodynamics and Geomaterials Research, University of Würzburg (samples preparation, X-ray fluorescence), at the GeoZentrum Nordbayern, University of Erlangen (trace element contents, LA-ICP-MS) and at FIERCE (Frankfurt Isotope & Element Research Center), Goethe University Frankfurt (apatite and zircon ages, LA-ICP-MS). Here, we present the full dataset of 55 whole-rock chemical analyses (X-ray fluorescence, LA-ICP-MS) from ten locations of the Heldburg dyke swarm.